2013
DOI: 10.5897/ijps12.714
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopic characterization of clay minerals from rocks of Lalibela churches, Ethiopia

Abstract: This study demonstrates the Fourier transform infrared (FTIR), Raman spectroscopy and scanning electron microscope -energy dispersive X-ray spectrometer (SEM-EDS) techniques which has been applied to characterize decay products and processes occurring at the surface of rock-hewn churches at the UNESCO's World Heritage site of Lalibela, Northern Ethiopia. Spectroscopic analyses comparing the observed frequencies with the available literature, minerals were identified. A special emphasis is devoted to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Low frequency peaks at 3620 cm -1 and 3619 cm -1 were prominent in all the samples. Single broad bands at 3650/3651 cm -1 , were observed in samples ED 1 and 2, indicative of poor structural order (Saikia and Parthasarathy, 2010;Kiros et al, 2013;Djomgoue and Njopwouo, 2013). Muscovite + quartz interference was identified in all the samples whereas iron oxides were prominent in ZEB 2, DUT 1, DUT 2, MK 1 and MK 2 but absent in ED 1 and ED 2.…”
Section: Thermal Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Low frequency peaks at 3620 cm -1 and 3619 cm -1 were prominent in all the samples. Single broad bands at 3650/3651 cm -1 , were observed in samples ED 1 and 2, indicative of poor structural order (Saikia and Parthasarathy, 2010;Kiros et al, 2013;Djomgoue and Njopwouo, 2013). Muscovite + quartz interference was identified in all the samples whereas iron oxides were prominent in ZEB 2, DUT 1, DUT 2, MK 1 and MK 2 but absent in ED 1 and ED 2.…”
Section: Thermal Analysismentioning
confidence: 91%
“…The OH bands in kaolin typically display four sharp stretching bands between 3600 and 3700 cm -1 namely; 3697, 3670, 3652/50 and 3620 cm -1 (Ekosse and Mulaba, 2008;Ekosse, 2008;Saikia and Parthasarathy, 2010;Kiros et al, 2013;Djomgoue and Njopwouo, 2013). The strong band at 3697 cm -1 arises from surface hydroxyls and produces an in-phase vibration perpendicular to the 1:1 layers (Ece et al, 2003).…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…The Fourier Transform Infra-Red spectrum and the vibrational band assignment for the HDTMAC-modified Ogwuta clay sample as presented in Fig. 7 and in Table 4 revealed that the peak at 671.25 cm -1 was due to Al-O-Si stretching while that at 771.55 cm-1 belongs to the Al-O-Fe bending in quartz [34]. The inner surface hydroxyl group (Al-OH-Al) deformation band was observed at 918.15 cm -1 and the bands associated with Si-O stretching, characteristic of kaolinite was 1010.75 cm -1…”
Section: Ftir Spectrummentioning
confidence: 99%